2005
DOI: 10.1256/qj.04.13
|View full text |Cite
|
Sign up to set email alerts
|

Microstructures and precipitation development in cumulus and small cumulonimbus clouds over the warm pool of the tropical Pacific Ocean

Abstract: SUMMARYIn situ airborne measurements obtained in convective clouds in the vicinity of the Marshall Islands on 15 days in July and August 1999 are used to determine the microphysical structures and precipitation-producing mechanisms in these clouds. The liquid water contents of the clouds were generally well below adiabatic values, even in newly risen turrets. This is attributed to the entrainment of ambient air and to the very efficient removal of cloud water by the collision and coalescence of drops. The form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
86
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(95 citation statements)
references
References 121 publications
8
86
1
Order By: Relevance
“…Chisnell and Latham, 1976;Harris-Hobbs and Cooper, 1987;Blyth and Latham, 1993;Rangno and Hobbs, 2005) and that by providing the initial graupel the freezing of supercooled drizzle/raindrops formed by the warmrain process can advance the onset of H-M (Phillips et al, 2001;Huang et al, 2008Huang et al, , 2011. The recent work by Lawson et al (2015) suggests secondary ice production associated with droplet freezing may also be an important mechanism for cloud glaciation, but we are not able to fully quantify how much influence it had on the clouds in this study based on our observations alone.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Chisnell and Latham, 1976;Harris-Hobbs and Cooper, 1987;Blyth and Latham, 1993;Rangno and Hobbs, 2005) and that by providing the initial graupel the freezing of supercooled drizzle/raindrops formed by the warmrain process can advance the onset of H-M (Phillips et al, 2001;Huang et al, 2008Huang et al, , 2011. The recent work by Lawson et al (2015) suggests secondary ice production associated with droplet freezing may also be an important mechanism for cloud glaciation, but we are not able to fully quantify how much influence it had on the clouds in this study based on our observations alone.…”
Section: Discussionmentioning
confidence: 74%
“…Several studies have observed such drops in the early stages of convective clouds (e.g. Koenig, 1963;Blyth and Latham, 1993;Rangno and Hobbs, 2005;Lawson et al, 2015), particularly in environments with a warmer cloud base. It is not clear if the supercooled raindrops are the first particles to freeze, or if they collide with primary ice particles produced from frozen cloud drops (e.g.…”
mentioning
confidence: 99%
“…This can explain (some of) the shapes of the larger ice particles in clouds [14][15][16] and of hailstone embryos [17,18]. It is believed that the fragmentation of freezing water droplets can play a role in the rapid glaciation of supercooled clouds and the development of precipitation [15,19,20]. Ice drop bursting has also recently been observed for condensation droplets formed on chilled super-hydrophobic surfaces, where the thrown out ice fragments can speed up frost formation [21].…”
mentioning
confidence: 93%
“…This is consistent with previous lab experiments [7,[9][10][11]24] in which a sharp decrease in the drop bursting probability is observed around this droplet size. Also field observations on natural clouds indicate that there exists such a size threshold [15,19,35].…”
mentioning
confidence: 99%
“…The first step is to distinguish the in-cloud and out-of-cloud data from the overall dataset. In fact, there is no generally acknowledged criterion to determine the appearance of clouds from the data, so that scientists use their own criterions in their researches [22,[35][36][37][38][39]. In addition, there is no comparison study to evaluate influences of using different criterions.…”
Section: Resultsmentioning
confidence: 99%